Indium, tin, and gallium doped CdSe quantum dots. - Tuinenga, Christopher J. (Kansas State University, 2011)
Doping quantum dots to increase conductivity is a crucial step towards being able to fabricate a new generation of electronic devices built on the “bottom-up” platform that are smaller and more efficient than currently available. Indium, tin, and gallium have been used to dope CdSe in both the bulk and thin film regimes and introduce n-type electron donation to the conduction band. CdSe quantum dots have been successfully doped with indium, tin, and gallium using the Li4[Cd10Se4(SPh16)] single source precursor combined with metal chloride compounds. Doping CdSe quantum dots is shown to effect particle growth dynamics in the “heterogeneous growth regime.” Doping with indium, tin, and gallium introduce donor levels 280, 100, and 50 meV below the conduction band minimum, respectively. Thin films of indium and tin doped quantum dots show improved conductivity over films of undoped quantum dots. Transient Absorption spectroscopy indicates that indium doping introduces a new electron energy level in the conduction band that results in a 70 meV blue shift in the 1Se absorption bleach position. Novel characterization methods such as in-situ fluorescence growth monitoring, single quantum dot EDS acquisition, static and time-resolved temperature dependant fluorescence spectroscopy were developed in the course of this work as well. These results show that doping CdSe quantum dots with indium, tin, and gallium has not only been successful but has introduced new electronic properties to the quantum dots that make them superior to traditional CdSe quantum dots.
Keywords: Doping; CdSe; Quantum dot; Chemistry (0485); Materials Science (0794)